Primary synovial sarcoma of the abdominal wall: A case report and review of the literature - Alsaif H Saif (Wolters Kluwer Medknow Publications, 2008)
Synovial sarcoma is a malignant mesenchymal neoplasm which commonly occurs in the extremities of adults, in close association with joint capsules, tendon sheaths, bursae and fascial structures. Only a few cases of synovial sarcoma occurring in the abdominal wall have been reported. A case of a primary synovial sarcoma arising from the anterior abdominal wall fascial aponeurosis is presented.